Studi Literasi Kimia yang Berkaitan dengan Etika Kimia Berdasarkan Fenomena Lokal Sehari-hari: Kasus Minyak Jelantah - Faiz Ilham Pratama; Nurfina Aznam; Eli Rohaeti (Postgraduate, University of Mataram, 2023)
Literation level, one of them is scientific literation, is possible to be the measurement of a national improvement in education. Scientific literation could be specified by chemistry literation which has four aspects; one of them is the affective domain. In this study, the research focuses on the affective domain consisting of five phases; phase of receiving, phase of responding, phase of valuing, phase of organizing, and phase of characterizing by value set. The study aims to describe the students' chemistry attitude skills related to hydrocarbon materials by integrating local case of everyday life. The local case taken is the cooking oil used in the â€œpenyetanâ€ stall. The research is descriptive qualitative research. The participants of this research are whole students of grade eleventh in a senior high school in Magelang who had been taught hydrocarbon materials. The sample of this research is 70 students of grade eleventh. Questionary is used in the research as a data collection method. The instrument used is a form of a questionnaire, which was a close-ended questionnaire with four possible answers; strongly disagree, disagree, agree, and strongly agree. The result shows the skill of chemistry attitude of hydrocarbon material is 69.12857%. It means that the student's skill chemistry attitude is in a category of fair.